The Maastricht Acute Stress Test (MAST): Physiological and Subjective Responses in Anticipation, and Post-stress - Shilton, Alexandra L.; Laycock, Robin; Crewther, Sheila G. (Frontiers in Psychology, 2017)
The Maastricht Acute Stress Test (MAST) is designed to be a simple, quick, and non-invasive procedure aimed at activating the human stress system. The MAST has been developed by combining elements from two of the most common experimental paradigms measuring stress, the Trier Social Stress Test (TSST) and the Cold Pressor Test (CPT). The aim of this study was to use the MAST procedure to elicit strong autonomic and subjective stress responses that can be quantified in terms of (systolic and diastolic) blood pressure, pulse rate, and state anxiety ratings. In healthy individuals, the MAST induced a significant elevation of systolic blood pressure (SBP) from baseline for up to 30 minutes post-MAST, while diastolic blood pressure (DBP) dropped to baseline within 10 minutes post-MAST. Interestingly, the presentation of instructions alerting participants to the procedure resulted in significant elevation of both SBP and DBP above baseline. However, BP measurements prior to test initiation were not as high as those measured immediately after the MAST procedure. Pulse rate data showed limited variability across time points. Self-reported state anxiety increased dramatically from baseline to immediately following the MAST procedure. Further, individuals who reported higher levels of depression and stress were more likely to demonstrate larger increases in SBP in response to the MAST. Together these results support the use of the MAST as a useful tool to activate both acute physiological and subjective measures of the stress response in healthy adults lasting up to 30 minutes.